Outcomes and Prognostic Factors of Radiation‐Induced and De Novo Head and Neck Squamous Cell Carcinomas. (8th March 2016) - Tay, Gerald Ci‐An; Iyer, N. Gopalakrishna; Ong, Whee‐Sze; Tai, David; Ang, Mei‐Kim; Ha, Tam Cam; Soo, Khee‐Chee; Tan, Hiang Khoon
Abstract : Objective: We sought to compare clinical outcomes, pathological features, treatment patterns, and survival outcomes between radiation‐induced squamous cell carcinoma (RISCC) and de novo SCC (DNSCC) of the head and neck, as well as identify prognostic factors in these patients. Study Design: Case‐control study. Setting: Tertiary medical center. Subjects and Methods: Retrospective case‐control analysis of 34 RISCCs and 136 DNSCCs matched by age at diagnosis, sex, smoking status, and primary tumor site. Results: Median latency of RISCC development was 13 years. Radiation‐induced squamous cell carcinomas were more likely to present with node‐negative disease than DNSCCs (70.6% vs 42.9%; P =. 024). A greater proportion of DNSCCs was treated with curative intent (92.6% vs 79.4%; P =. 048) and achieved no residual disease posttreatment (82.2% vs 41.2%; P <. 001) compared with RISCCs. Patients with RISCC had poorer overall survival (OS) (median, 1.67 vs 5.03 years; P =. 018) and disease‐specific survival (DSS) (median, 1.67 vs 8.65 years; P =. 001) than those with DNSCC. Among patients who underwent curative treatment with no residual disease after treatment, there were, however, no survival differences between RISCC and DNSCC. Conclusion: In our cohort, RISCCs have a poorer prognosis than DNSCCs. However, those able to undergo curative treatment and have no residual disease after treatment have comparable survival outcomes. Locoregional control of these tumors appears paramount in achieving the best outcomes for patients with RISCC.